Real-time dashboard monitoring and alerting system for compressed air supply in rubber compound manufacturer - Thepmanee, Teerawat; Ngamsangiam, Pornprasert; Sittigorn, Jirasak; Pongswatd, Sawai (My University, 2020)
To minimize unexpected disruptions resulting from air supply problems in manufacturing production, a continuous monitoring of air pressures is crucial for predicting and preventing significant issues that may arise. This paper proposes a technique to build a real-time dashboard monitoring and alerting system for improving an availability of existing compressed air supply in a rubber compound manufacturer in Thailand. Flow and pressure transmitters as well as motorized ball valves are installed in the ma-jor supply lines of air piping system. In addition, a 3-phase power and energy meter is also installed to measure key electrical parameters of two main air compressors. The proposed technique is based on the use of cost-effective Node-RED web application not only to monitor volumetric flow rate, air pressure values, valve statuses, input/output module statuses, and energy-related parameters on the created dashboard in real time but also to alert plant personnel to pressure readings that fall outside an acceptable range via the LINE Notify application. There are three different notification patterns depending on how long is the pressure reading value out of the acceptable range. Moreover, the on/off status of all ball valves can also be remotely set on the dashboard subpages. Experimental results verify that the improved system can be utilized to assist plant personnel in trou-bleshooting and solving the problems with compressed air supply.
Keywords: Alerting; Availability; Compressed air; Dashboard; Monitoring; Pressure measurement; Web application